Developement and validation of flourishing questionnaire based on seligman's model among Iranian university students - Samira Soleimani; Ali Mohammad Rezaei; Farahnaz Kianersi; Hanie Hojabrian; Kokab Khalili Paji (Gonabad University of Medical Sciences, 2015)
The main purpose of this study was designing a questionnaire to measure human flourishing based on Seligman's model. Therefore, based on an extensive literature review of existing measures, an initial questionnaire with 50 questions was prepared. Sample was selected randomly in two stages. In the initial stage, a sample of 50 people were selected in order to assessment the reliability, and then a sample of 400 for performing factor analysis. According to the results of factor analysis, the 28 items which were positively correlated with the total test and at least had a factor loading of 35/0 or higher on a factor, were selected for the final questionnaire. The questionnaire of 28 items, was named human flourishing. Validity of the human flourishing questionnaire (HFQ) was calculated via the correlation coefficient of this scale with "The Ahvaz self-actualization questionnaire ", Diener's flourishing questionnaire and depression questionnaire of Beck. Accordingly, a four-factor structure was achieved including positive emotions, relationships, meaning, and achievement. In addition, the HFQ's reliability was determined using internal consistency (Cronbach's alpha). The result in this study showed that FQ has satisfactory reliability and validity coefficients so can be used in psychological research and measuring studies in order to measure human flourishing.